PGMI Students' Perceptions of the Implementation of Artificial Intelligence (AI) Technology in Learning in Madrasah Ibtidaiyah - Samiha, Yulia Tri; Aksara, Langit (FKIP - Universitas Riau, 2025)
The development of Artificial Intelligence (AI) technology in the era of the Industrial Revolution 4.0 has a significant impact on the world of education, including in Madrasah Ibtidaiyah (MI). This transformation demands the readiness of teachers, especially prospective madrasah teachers, to adopt the technology without ignoring Islamic values. This study aims to explore the perceptions of Madrasah Ibtidaiyah Teacher Education (PGMI) Study Program students towards the implementation of AI technology in learning in MI. The study used a descriptive qualitative approach with the participation of 40 PGMI students of UIN Raden Fatah Palembang. Data were collected through an open-ended questionnaire and analyzed using thematic analysis method with the help of NVivo 14 software. The results showed that students have a fairly good understanding of AI as an intelligent technology that supports personalized and interactive learning. The main challenges in implementing AI in MI include limited infrastructure, funding, digital literacy, and resistance to change. Students emphasized the importance of mastering technology skills as a core competency of prospective MI teachers. This study recommends the integration of AI-based technology training in the PGMI curriculum to prepare adaptive and competent educators in the digital era.